An Experimental Study of Healthy Diet and Physical Activity on Students - Mottakin Ahmed; Sanjay Kumar Mehra; Vikas Saxena (Performa, 2026)
Purpose. To study the effect of a healthy diet and physical activity program. Method A pre-experimental and post-experimental single group study design. Set up: The study was conducted at an educational institution in Bhopal, Madhya Pradesh. Results: A total of 200 students participated in the study. Result. Dietary habits were assessed using different food components before and after the intervention. Healthy food intake such as milk increased from (1.92) to (2.625), vegetables from (2.97) to (3.40), fruits from (1.4795) to (2.2715), cereals from (2.987) to (5.02), and pulses from (1.985) to (2.2794). All these improvements were statistically significant with high t-values (p<0.05). Flesh group consumption slightly decreased from (0.4364) to (0.3676) but was still significant. However, bakery/snacks/sweets (0.3815 to 0.3384), fast food (0.2163 to 0.2005), and nuts (0.3216 to 0.3506) showed non-significant changes, indicating limited impact of intervention on these items. Physical activity also improved significantly. Minutes of activity increased from (158.21) to (182.34) with a t-value of (4.6), and METs increased from (671.18) to (767.95) with a t-value of (2.7), both statistically significant at 0.05 level. This indicates improvement in both duration and intensity of physical activity. Conclusions. The study concludes that an healthy diet combined with physical activity significantly improves dietary habits and physical activity levels.